PHOTOCHEMICAL SELF-PURIFICATION OF AQUATIC SYSTEMS IN THE PRESENCE OF VITAMIN B₆ - GLADCHI, Viorica; BLONSCHI, Vladislav; DUCA, Gheorghe; LIS, Angela; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2026)
Vitamin B6 (pyridoxine, PN) released from anthropogenic and biogenic activities can influence the chemical self-purification of surface waters through its photochemical transformations. The present study aimed to investigate the kinetics and mechanisms of pyridoxine photodegradation under conditions that partially simulate the natural environment (pH ~7, aerated medium) using simulated solar irradiation. Three model systems were investigated: (1) PN–hν; (2) PN–H2O2–hν; (3) PN–H2O2–Cu(II)–hν, using direct spectrophotometry (λ = 328 nm). The kinetic parameters determined included partial reaction orders (using the van’t Hoff method), effective rate constants, and half-lives (τ₁/₂). Direct photolysis of PN follows a partial reaction order of 0.2 with respect to [PN], with k = (5.38±0.26)·10-4 s-1 and τ₁/₂ = 21±0.5 min. However, the low quantum yields (7.31–10.70)·10-3 indicate that direct photolysis of vitamin B6 is negligible under natural aquatic conditions. In the presence of H2O2, the partial reaction orders are 0.3 (PN) and 0.7 (H2O2), with W = k·[PN]0.3·[H2O2]0.7, k = (3.69±0.11)·10-4 s-1 and τ₁/₂ = 31.1±0.30 min. For PN–H2O2–Cu(II), the partial reaction orders are 0.2 (PN), 0.4 (H2O2), and 0.3 (Cu2+) with k = (3.91±0.17)·10-4 s-1, and τ₁/₂ = 29.2±0.53 min. In conclusion, PN undergoes measurable photodegradation under simulated natural conditions.